Studies on structural and electrical properties of Mg0. 5+y (Zr2-yFey) 2 (PO4) 3 ceramic electrolytes - Anuar, N.K.; Adnan, S.B.R.S.; Jaafar, M.H.; Mohamed, N.S. (Springer Verlag (Germany), 2016)
The sample of Mg0. 5+y (Zr1-y Fey) 2 (PO4) 3 (0.0 ≤y ≤0.5) was synthesized using the sol-gel method. The structures of the samples were investigated using X-ray diffraction and Fourier transform infrared spectroscopy measurement. XRD studies showed that samples had a monoclinic structure which was iso-structured with the parent compound, Mg0.5Zr (PO4) 3. The complex impedance spectroscopy was carried out in the frequency range 1–6 MHz and temperature range 303 to 773 K to study the electrical properties of the electrolytes. The substitutions of Fe3+ with Zr4+ in the Mg0.5Zr (PO4) 3 structure was introduced as an extrainterstitial Mg2+ ion in the modified structured. The compound of Mg0.5+y (Zr1-y Fey)2(PO4)3 with y = 0.4 gives a maximum conductivity value of 1.25 × 10−5 S cm−1 at room temperature and 7.18 × 10−5 S cm−1 at 773 K. Charge carrier concentration, mobile ion concentration, and ion hopping rate are calculated by fitting the conductance spectra to power law variation, σac(ω) = σo  + Aωα. The charge carrier concentration and mobile ion concentration increases with increase of Fe3+ inclusion. This implies the increase in conductivity of the compounds was due to extra interstitial Mg2+ ions.